Lily and the shining dragons - Webb, Holly (London : Orchard, 2012)
Forbidden magic users Lily and her sister Georgie are on the run and find themselves trapped in a school where magical children are hidden away.
5.7
3-6.
3-6
Keywords: Magic -- Juvenile fiction; Magicians -- Juvenile fiction; Sisters -- Juvenile fiction; Fantasy; Magic -- Fiction; Magicians -- Fiction; Sisters -- Fiction; Magic -- Fiction; Magicians -- Fiction; Sisters -- Fiction; Fantastic fiction; Fantastic fiction